Strategi Pengelolaan Laba Harian dalam Meningkatkan Keberlanjutan Usaha Pedagang Pasar Kembangsari, Kecamatan Tengaran - Lahagu, Eduard Emerik; Hendrajaya, Hendrajaya (Mahesa Research Center, 2025)
This article aims to analyze the challenges in managing daily profits faced by traders in Kembangsari Market and the factors that support the sustainability of their businesses. The problem focuses on the main obstacles that affect profit management, such as fluctuations in the price of goods, difficulty in obtaining additional capital, lack of financial literacy, and competition with modern retailers. To approach this problem, this study uses the theory of small business financial management and a business sustainability approach. Data were collected through direct observation and in-depth interviews with traders and analyzed qualitatively. The results of the study indicate that although traders have a fairly good profit recording and allocation strategy, they still face various obstacles that have the potential to hinder business growth. However, family support, utilization of technology, education and training, and networks with suppliers are supporting factors for the sustainability of their businesses. This study concludes that better strategies in financial recording, wider access to capital, business digitalization, and product diversification can help traders in Kembangsari Market increase their profitability and competitiveness amidst existing challenges.